Nutrient recovery from swine wastewater at full-scale: An integrated technical, economic and environmental feasibility assessment. (August 2021) - Shim, Soomin; Reza, Arif; Kim, Seungsoo; Won, Seunggun; Ra, Changsix
Abstract: In this study, the technical, economic and environmental attributes of a full-scale nutrient recovery process connected to the centralized swine wastewater treatment facility (CSWTF) were evaluated. The performance of the process was assessed by introducing influent to the recovery reactor from different components of the CSWTF such as sedimentation tank (swine wastewater) and biological treatment reactor (biologically oxidized material and supernatant of the biologically oxidized material). The results of technical performance assessment revealed that the O–P recovery (87.1–90.7%) and NH4 –N removal (66.9–72.1%) efficiencies from the influent of biological treatment reactor were significantly higher than the influent from sedimentation tank (81.7 and 19.8%, respectively, p  < 0.05). The economic evaluation elucidated that by increasing the treatment capacity of the recovery reactor from 30 m 3 /d to 100 m 3 /d, operating expenses could be covered through the commercialization of struvite, while it would take around seven years to get back the capital investment. Additional economic savings could also be possible when using the recovered struvite as a fertilizer raw material along with other environmental benefits. Considering the current farming practices in Korea, the complete recovery of O–P from CSWTFs as struvite could drop the soil phosphorus surplus by 40%, minimize the phosphatic fertilizer consumption by 6.4% and ultimately reduce CO2 equivalent emissions of 6522 tons/year in comparison to chemical fertilizer production. However, during the continuous operation of the full-scale nutrient recovery process, influent characteristics need to be incessantly monitored and adjusted to the optimum conditions to improve the economics of recovered products. Overall, the nutrient recovery process at full-scale not only solves the problem of treating highly polluted swine wastewater but also helps to ensure societal and environmental sustainability. Highlights: One of the first studies on performance evaluation of a full-scale nutrient recovery process from swine wastewater. O–P recovery efficiency through struvite crystallization ranges from 81.7% to 90.7%. Influent nutrient concentrations and treatment capacity govern economic efficacy. Struvite as alternative fertilizer can effectively reduce soil P surplus.